Trigonometric widths of the classes B_p,θ^ r of functions of many variables in the space L_q - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We obtain estimates exact in order for the trigonometric widths of the Besov classes B_p,θ^ r of periodic functions of many variables in the space L_q for 1 ≤ p ≤ 2 < q < p/(p - 1).